How does push-off distance influence force-velocity profile and performance during vertical jumping? - Pommerell, F.; Boyas, S.; Samozino, P.; Morel, B.; Begue, J.; Rahmani, A.; Peyrot, N. (Journal of Applied Biomechanics, 2025)
In many sports, practitioners must reach their maximal jump height (hmax) under time constraints. This requires a reduction of the countermovement depth and so of the push-off distance (hPO). The purpose of this study was to investigate how hPO influences force-velocity (F-v) profiles ( F0, v0, Pmax, and SFv) and performance. Eleven participants (age: 26 [5] y, height: 175.6 [11.2] cm, mass: 76 [15] kg; squat 1RM: 129 [34] kg) performed maximal countermovement jumps. Kinetic and kinematic measurements were used to assess individual F-v profiles for three different hPO conditions (hPO-SMALL, hPO-MEDIUM, hPO-LARGE) from countermovement jumps performed under different load conditions (bodyweight [BW], BW + 8 kg, BW + 17 kg, BW + 40% 1RM, BW + 70% 1RM). Results indicated that F0 and Pmax changed across hPO conditions, while v0 remained constant. A lower hPO led to a significantly higher F0 and Pmax. These changes resulted in a steeper SFv leading to a more force-oriented profile, a lower optimal SFv, and a greater F-v imbalance. Reducing hPO and modifying F-v profile led, to some extent, to a reduction in hmax. Performance is a compromise between hPO, Pmax, and F-v imbalance, all influenced by countermovement depth. This explains why reducing countermovement depth to meet time constraints may lower performance.